2008
DOI: 10.1590/s1980-57642009dn20100008
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal atrophy and verbal episodic memory performance in amnestic mild cognitive impairment and mild Alzheimer's disease: A preliminary study

Abstract: To evaluate hippocampal volume in patients with AD and aMCI, and correlate its atrophy with verbal episodic memory performance.MethodsWe studied 42 individuals older than 50 years, including 14 with amnestic mild cognitive impairment (aMCI), 14 with mild Alzheimer’s disease (AD) and 14 normal controls. All individuals were submitted to the Rey auditory verbal learning test (RAVLT) to evaluate episodic memory. They were also submitted to the forward (FDS) and backward digit span (BDS) subtest of WAIS-R to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The aMCIdementia conversion rate is 10-15% per year, compounding to 80% after 6 years (Petersen, 2000;Petersen et al, 2001). Previous behavioral studies had identified that patients with aMCI showed declined neurocognitive function associated with episodic memory, including immediate and delayed recall, and such poor performance in memory significantly correlated with reduced hippocampal volume compared with healthy older adults (Marchiani et al, 2008;Salmon, 2012;Gainotti et al, 2014). The failure of these basic memory functions for older adults lead to the difficulties in maintaining activities of daily living, the subsequent loss of independence, and the reduction of physical as well psychological health.…”
Section: Introductionmentioning
confidence: 99%
“…The aMCIdementia conversion rate is 10-15% per year, compounding to 80% after 6 years (Petersen, 2000;Petersen et al, 2001). Previous behavioral studies had identified that patients with aMCI showed declined neurocognitive function associated with episodic memory, including immediate and delayed recall, and such poor performance in memory significantly correlated with reduced hippocampal volume compared with healthy older adults (Marchiani et al, 2008;Salmon, 2012;Gainotti et al, 2014). The failure of these basic memory functions for older adults lead to the difficulties in maintaining activities of daily living, the subsequent loss of independence, and the reduction of physical as well psychological health.…”
Section: Introductionmentioning
confidence: 99%
“…For example, most studies simplify recognition memory assessment by only registering the number of correct identifications (i.e., ‘‘hits'') [15]. Other researchers report a corrected measure: hits minus false alarms [16,17], or percent of correct recognitions [18,19] or through nonparametric methods [20]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, previous work in this area found that list learning was better at distinguishing cognitively normal individuals from those with MCI, as compared to story memory (Rabin et al, 2009). Although studies have found associations between individual episodic memory tests and hippocampal volumes in cognitively normal older adults (Hackert et al, 2002;Rosen et al, 2003;Zimmerman et al, 2008) and in individuals with AD (Marchiani, Balthazar, Cendes, & Damasceno, 2008;Sarazin et al, 2010), direct comparisons between structured and unstructured verbal memory tests in terms of their association with underlying cortical areas are limited. Ezzati et al (2016) found that, among cognitively healthy older adults, list learning performance was associated with total and left hippocampal volume, whereas paragraph recall was not significantly related to hippocampal volumes, consistent with other studies in healthy older adults (Marquis et al, 2002;Rodrigue & Raz, 2004).…”
Section: Introductionmentioning
confidence: 99%